(untitled) (Bangladesh Journal of Botany, 2021)
Effects of L-ornithine (150 mg/l) on the germination, seedling growth, mitotic index, chromosome aberrations and micronucleus frequency of Allium cepa L. bulbs germinated at 0.125 M salinity were studied. The radicle number of the group III bulbs germinated in the medium with ornithine alone as compared to ones of the group I (control) bulbs which germinated in distilled water medium. But, their germination percentage, radicle length and fresh weight were statistically the same as ones of the group I bulbs. Besides, the micronucleus frequency and chromosomal abnormalities in the root-tip meristematic cells of the group III bulbs showed increased germination compared to ones of the group I bulbs. However, their mitotic index statistically showed the same value as the group I bulbs. Salt stress significantly inhibited the germination and seedling growth of A. cepa bulbs. Moreover, it reduced the mitotic index in the root-meristem cells of the bulbs and fairly increased the number of chromosome aberrations and micronucleus frequency. On the other hand, the inhibitive effect of salt on the germination, seedling growth, mitotic index and micronucleus frequency was dramatically alleviated in varying degrees by ornithine application. But, it was ineffective in reducing the detrimental effect of salinity on the chromosome aberrations. The germination percentage, radicle lenght, radicle number, fresh weight, mitotic index, micronucleus frequency and chromosomal aberrations of the group II seedlings grown in 0.125 M salinity were 27%, 13.5 mm, 18.4, 7.1 g, 5.5, 18.3 and 60.8%, respectively while these values became 68%, 16.4 mm, 16.4, 10.5 g, 15.6, 7.6 and 74.8% in the group IV seedlings treated with L-ornithine. Bangladesh J. Bot. 50(4): 1165-1171, 2021 (December)